Les relations économiques États-Unis / Amérique latine pendant les années Bush : la nouvelle donne - Martine Azuelos (Revue LISA)
While George W. Bush’s election had promised to revive the drive towards further economic integration in the Americas, as he was leaving office eight years later the achievements of his presidency seemed rather mixed and the future of U.S.-Latin America relations uncertain. To shed light on this turnaround, this paper sets the Bush years in the wider context of post-Cold War renewed U.S. emphasis on the economic dimension of its relationship to Latin America. The first part, which focuses on quantitative data, concludes that although two-way trade and capital flows did grow significantly between 2000 and 2007, the momentum of the 1990s was largely lost. In an attempt to account for this trend, the second part focuses on the geopolitical and geoeconomic background which led to the United States’ relations with Latin America taking a new direction after 2001.